Findings of a Naloxone Database and its Utilization to Improve Safety and Education in a Tertiary Care Medical Center. Issue 3 (7th January 2015) - Rosenfeld, David M.; Betcher, Jeffrey A.; Shah, Ruby A.; Chang, Yu‐Hui H.; Cheng, Meng‐Ru; Cubillo, Efrain I.; Griffin, Julia M.; Trentman, Terrence L.
Abstract: Introduction: Analyzing hospital naloxone use may assist in identification of areas for quality and safety improvement. Our primary objective is to quantitate the incidence of hospital naloxone use and to assess certain patient populations at risk. Methods: During the years 2008 to 2011, each clinical scenario where naloxone was administered on an in‐patient care ward was reviewed. The events were assessed to separate situations where naloxone rescue was effective in reversing opioid‐induced intoxication vs. others. Further analysis was conducted to stratify patient populations at greatest risk. Results: Naloxone was administered for well‐defined opioid‐induced respiratory depression and oversedation 61% of the time, the remainder used for patient deterioration of other etiology. Surgical populations are at risk with an incidence of 3.8/1, 000 hospitalized patients, and this is the greatest within 24 hours of surgery. General surgical patients represent the highest surgical patient risk at 5.5/1, 000. Medical patients represent lower risk at 2.0/1, 000. Patients with patient‐controlled analgesia and epidural opioid infusion are high risk at 12.1 and 13.1/1, 000 patients, respectively. Many quality and safety interventions were gradually implemented in response to this data and are summarized. These include nursing and provider education, electronic medical record modification, and more stringent patient monitoring practices. Conclusion: Examination of naloxone use can assist in the identification and stratification of patients at risk for opioid‐induced respiratory depression and oversedation and can serve as a driver for improvements in hospital patient safety. This information can also guide other institutions interested in similar improvements.